Stating and solving digital image similarity problem - Morkevičius, Nerijus; Valantinas, Jonas (Lietuvos matematikos rinkinys, 2001)
Digital image similarity problem is posed. Necessary conditions (criterion) for the existence of similar digital d-dimensional images are formulated and proved. Areas of application of the criterion are mentioned.